Pengaruh Jenis Sambungan Pipa Elbow 90Â° dan Short Bend Terhadap Head Loss Pada Sistem Perpipaan - Bambang Kurniawan, Basuki, Mochamad Arif Irfa`'i (Universitas Hasyim Asy'ari, 2020)
The environment around us will not be far from the flow of fluids to meet the needs of life. For example, a series of PVC pipes used to distribute water at home, of course, has losses caused by its components, one of which is the pipe bend connection. One of the energy losses in changing the pipe cross section is the pressure loss. The pressure loss can be affected by the flow rate of the fluid and the magnitude of the bend connection of the pipe. The research in this thesis was carried out in the Mechanical Engineering laboratory of Hasyim Asy'ari University. This research is quantitative in nature which will discuss about the pressure loss in elbow pipe bends or broken and short pipe bends with a cross-sectional size of 1 terhadap inches to the value of pressure loss. The results showed that the greatest value of pressure loss was in the bend of the elbow or broken pipe, which was 0.002206 m, while the smallest value of pressure loss was in the bend of the short pipe which had a value of 0.00000332 m. So the conclusion of this pressure loss research is that the greater the r/d value of the pipe bend, the smaller the pressure loss value.